Workload Indicators of Staffing Need as a tool to determine nurse staffing for a high volume academic Emergency Department: An observational study. (September 2019) - Wundavalli, LaxmiTej; Kumar, Parmeshwar; Dutta, Samarpita
Highlights: WISN: Workload Indicators of Staffing Need. WISN: simple, easy to use, can prospectively measure all nursing activities. WISN useful tool to translate workload into nursing full time equivalents for ED. Skill mix ratio of 82% nurses to 18% non nursing assistants recommended for ED. 125 nurses (total available working time: 187, 250 h) needed for 105, 103 patients. Abstract: Introduction: Determination of staffing requirement for an Emergency Department (ED) is often difficult due to random arrivals of a complex mix of cases, fluctuating volumes and lengths of stay. Most staffing strategies are based on patient census, lengths of stay, patient dependency or patient classification systems. However, the actual quantity of workload is seldom employed as a basis to calculate staffing. Aim: The aim of this study was to determine the requirement of nurses for a high volume academic ED and to suggest measures to optimally schedule them. Methodology: Structured interviews were held with ED nurses to list their health service activities, support and additional activities. Time taken for the activities was calculated based on observations and interviews. Records were perused to obtain annual service statistics. Workload Indicators of Staffing Need (WISN) described by World Health Organization was utilized to analyze and determine staffing need. Results: The study identified 34 health service activities, 21 support activities and 3 additional activities to be performed by 125 nurses with a total available working time of 187, 250 h for an annual volume of 105, 103 patients. The WISN ratio was 0.90 which indicates that the current staff strength was inadequate. The Emergency Department requires 13 more full time staff nurses for it to function optimally. In case of reallocation of certain relevant duties to phlebotomists or nursing assistants, the requirement of staff nurses is 102. Consequently, a skill mix ratio of 82% nurses to 18% nursing assistants and phlebotomists is suggested. Discussion: The Workload Indicators of Staffing Need is a simple, easy to use method that can prospectively measure direct and indirect nursing activities and translate workload into nursing full time equivalents for the ED. This method is also useful to identify activities that do not require nursing professional skills and prescribe the skill mix of staff.